Patrimonialisation de la nature abiotique et mise en tourisme : l’exemple des Géoparcs mondiaux UNESCO - François Bétard; Édith Fagnoni (Bulletin de l’Association de Géographes Français)
UNESCO Global Geoparks are labelled territories with a rich geoheritage of international relevance, on which a territorial project is based, with engagement and empowerment of territorial actors and local communities. Officially awarded by UNESCO since 2015, this new label offers the opportunity to examine the relationships between environment and heritage through the prism of a non-living or abiotic nature, subject to a heritage-making process generated by a complex interplay of stakeholders. This paper addresses the making-process of geoheritage in territories seeking recognition, with selected examples of Geoparks located in France and other countries. The authors also address the question of tourism development on geosites and its specificities, as well as the tensions that can result from the heritage processes, between the need for conservation and the legitimacy of territorial development, thus highlighting the ambivalences of the labelling process.